1988
DOI: 10.1021/ac00154a001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of nitro-polynuclear aromatic hydrocarbons in air and diesel particulate matter using liquid chromatography with electrochemical and fluorescence detection

Abstract: Three different approaches to the liquid chromatographic detection of nitro polynuclear aromatic hydrocarbons In air and diesel particulate extracts are presented, based on differential pulse (LCDPD) and amperometrlc (LCEC) electrochemical detection and fluorescence detection following online reduction to the amine (LCFI). The particulate extractlon/fractlonatlon procedure for each detection approach Is discussed. The operational advantages of oxygen removal with a platinum oxygen scrubber (aM three types of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(47 citation statements)
references
References 44 publications
3
41
0
2
Order By: Relevance
“…The nitroarenes formed from the OH radical-initiated reactions of the PAH (Table 3) those observed in direct emissions such as diesel exhaust particles. For example, the most abundant nitro-isomers of pyrene, fluorene, and fluoranthene observed in diesel exhaust are 1-nitropyrene, 2-nitrofluorene, and 3-nitrofluoranthene, respectively (62)(63)(64)(65), while the isomers formed from the gas-phase OH radical-initiated reactions of these PAH are 2-nitropyrene (9,14), 3-nitrofluorene (58), and 2-nitrofluoranthene (9,14), respectively. To date, there is no convincing evidence for significant artifact formation of nitro-PAH during atmospheric sampling, at least when using standard high-volume samplers (66).…”
Section: H-chohmentioning
confidence: 99%
“…The nitroarenes formed from the OH radical-initiated reactions of the PAH (Table 3) those observed in direct emissions such as diesel exhaust particles. For example, the most abundant nitro-isomers of pyrene, fluorene, and fluoranthene observed in diesel exhaust are 1-nitropyrene, 2-nitrofluorene, and 3-nitrofluoranthene, respectively (62)(63)(64)(65), while the isomers formed from the gas-phase OH radical-initiated reactions of these PAH are 2-nitropyrene (9,14), 3-nitrofluorene (58), and 2-nitrofluoranthene (9,14), respectively. To date, there is no convincing evidence for significant artifact formation of nitro-PAH during atmospheric sampling, at least when using standard high-volume samplers (66).…”
Section: H-chohmentioning
confidence: 99%
“…Os hidrocarbonetos aromáticos polinucleares (HPA) formados durante a combustão incompleta de materiais contendo carbono, em especial carvão e derivados do petróleo, mesmo na baixa concentração em que geralmente se apresentam, afetam incisivamente o equilíbrio atmosférico 3,16 . Esses hidrocarbonetos também sofrem reações de nitração [25][26][27] e oxidação atmosféricas 3 , cujos produtos possuem efeito genotóxico 28 , além de produzirem fototoxinas que participam da destruição de florestas 2,3 . Considerando-se que, diariamente, cerca de 12 m 3 (15 kg) de ar são inalados pela maioria dos indivíduos, quantidade essa que pode variar com a idade e nível de atividade de cada pessoa, é de se esperar que a qualidade da respiração afete o funcionamento do metabolismo celular do organismo e, portanto, a saúde do indivíduo 1,3 .…”
Section: A Poluição Atmosférica E Suas Conseqüências Na Saúde Públicaunclassified
“…Os hidrocarbonetos aromáticos polinucleares (HPA) formados durante a combustão incompleta de materiais contendo carbono, em especial carvão e derivados do petróleo, mesmo na baixa concentração em que geralmente se apresentam, afetam incisivamente o equilíbrio atmosférico 3,16 . Esses hidrocarbonetos também sofrem reações de nitração [25][26][27] …”
unclassified
“…[3][4][5] Yet, few studies on the reductive detection of aromatic nitro compounds are to be found in the literature. [6][7][8] This is mainly because deoxygenation of the medium must be carried out for electrochemical detection in a cathodic mode.…”
mentioning
confidence: 99%
“…[3][4][5] Yet, few studies on the reductive detection of aromatic nitro compounds are to be found in the literature. [6][7][8] This is mainly because deoxygenation of the medium must be carried out for electrochemical detection in a cathodic mode. 3,[9][10][11][12] Otherwise, dissolved oxygen, whose potential for reduction is quite low at common electrodes such as carbons, exhibits a cathodic response, preventing the sensitive and reproducible determination of analytes.…”
mentioning
confidence: 99%